ERRORS ANALYSIS IN PASSIVE VOICE AT UNDHIRA STUDENTSâ€™ THESES AGREED FOR FOLLOWING THE FINAL COMPREHENSIVE TEST - Kamayana, I Gusti Nyoman Putra (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2022)
ABSTRACT This article is part of the writerâ€™s study on the grammatical error analysis. It is the study on studentsâ€™ theses as the final academic projects for getting the bachelor degree at English Department of Universitas Dhyana Pura Bali. The students were allowed for joining final comprehensive test, to write their studies by using right grammar. However, they still wrote errors writing. Propose of this study identified the types and percentage of grammatical errors in using passive voice. It was made by the students in their writing products in terms of studies agreed by their advisors for following the final comprehensive test. This study was done by applying descriptive research design. The total member of this study was the documents in the form of 30 studentsâ€™ studies. They were agreed for following the final comprehensive test in three periods of final comprehensive tests from 2018/2019 up to 2020/2021. Random sampling technic was made use of collecting 3 studies (about 10% of the population) as the sample. In getting the data, researcher read and analyzed all of 3 studentsâ€™ studies. It was found that the students wrote errors in using passive voice in each types of surface strategy taxonomy. The highest level of the grammatical errors on passive usage in on â€œOmissionâ€ type. The omission in preposition, to be, conjunction, and verbal. It indicated that the students still have got problem in using passive voice. The lecturers of grammar are suggested to pay more attention and consider the appropriate teaching technique in teaching in passive voice. This study is also recommended to studentsâ€™ advisors to give more checking on the studentsâ€™ errors for the accompaniment process of their studentsâ€™ errors, particularly in making use of passive voice. Kata kunci: grammatical error analysis, passive voice, studentsâ€™ theses.